Why require ethics in engineering? - Flumerfelt, Shannon (Animo Repository, 2021)
This theoretical paper will provide a review of the literature regarding the need for ethics in the workplace and how taxonomical ethical development can be used in engineering education. In fact, advocacy to educate for ethics in engineering education by design is discussed as a solution to this problem. By spiraling ethical competency development into engineering education as a body of practice, rather than as a theory of knowledge, it is possible to integrate engineering hard science content with engineering soft science competency. This means that current programs' scopes and sequences may remain in place, with recommended changes in pedagogy. Copyright © 2012 by ASME.